Australian Research Libraries and the Research Quality Framework - Haddow, Gaby (2006)
The Federal Government is introducing a new funding model for research in Australian higher education institutions, the Research Quality Framework (RQF). It will require university research groups to submit evidence of research quality and impact in order to receive funding. This paper will look at the likely impact of the RQF on libraries in Australia, based on experience gained through an RQF trial and from reports and research from the United Kingdom, where a similar funding model, the Research Assessment Exercise (RAE), has been operating for a decade.When Curtin University participated in an RQF trial in 2005 library staff provided extensive support to academics seeking information about their publications. Workshops were delivered to demonstrate important sources of information and individual assistance was given as requested. Indicators of research impact, such as journal impact factors, and the importance of 'quality' publications, has resulted in heightened interest in publishing generally, and citation indexes in particular, among many academics. The UK's RAE experience suggests a range of issues will emerge as the RQF model is implemented. For example, an increase in articles submitted for publication by academics has led to concerns about the quality and number of journals, and the effects on subscription prices. Research examining the relationship between RAE ratings and academic library funding and discussion about methods for evaluating journal use in libraries illustrate how the RAE is being considered in the UK. The paper will conclude by bringing these issues together with suggestions for planning library services in the context of RQF implementation in Australia.